2001
DOI: 10.1103/physrevlett.86.5349
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Metal-Insulator Transition in a Switchable Mirror

Abstract: Rare earth hydride films can be converted reversibly from metallic mirrors to insulating windows simply by changing the surrounding hydrogen gas pressure at room temperature. At low temperatures, in situ doping is not possible in this way as hydrogen cannot diffuse. However, our finding of persistent photoconductivity under ultraviolet illumination offers an attractive possibility to tune yttrium hydride through the T 0 metal-insulator transition. Conductivity and Hall measurements are used to determine critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 26 publications
1
25
1
Order By: Relevance
“…This is notably different compared to hitherto reported transitions. [18][19][20][21][22] Potential applications of the reversible transition MAlSi-MAlSiH, however, will be hampered by the relatively high formation and desorption temperatures of the hydrides. On the other hand, the hydrides MAlSiH could reveal interesting properties inherent to the noncentrosymmetric layer structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is notably different compared to hitherto reported transitions. [18][19][20][21][22] Potential applications of the reversible transition MAlSi-MAlSiH, however, will be hampered by the relatively high formation and desorption temperatures of the hydrides. On the other hand, the hydrides MAlSiH could reveal interesting properties inherent to the noncentrosymmetric layer structure.…”
Section: Discussionmentioning
confidence: 99%
“…17 Reversible hydrogen-induced metal-nonmetal transitions occur rarely and systems displaying this phenomenon have attracted attention as switchable mirror systems when the nonmetal is a large band-gap semiconductor. [18][19][20][21] This is the case for YH 2 -YH 3−x or LaH 2 -LaH 3−x , where the dihydrides are good metals, or Mg 2 Ni-Mg 2 NiH 4 . Although the metallic component absorbs hydrogen near ambient conditions, the transition is usually accompanied with a major reconstruction of the metal-atom arrangement because the nonmetallic state implies the presence of covalently bonded or hydridic hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, yttrium hydride films also exhibit photochromic (PC) behavior, i.e., the optical properties of the films change reversibly when illuminated by light of adequate energy (wavelengths in the blue or UV range). Early works by Hoekstra et al [11] have shown a light induced metal insulator transition in yttrium hydrides at low temperature, and Ohmura et al [6,12] accidentally discovered PC behavior in yttrium hydride films subjected to high pressure. Later, Mongstad et al [13,14] reported PC behavior in transparent oxygen-rich yttrium hydride films under atmospheric conditions and at room temperature.…”
mentioning
confidence: 99%
“…The special characteristics of these mirrors is that they can be continuously and reversibly switched between a metallic reflecting state to an insulating transparent state by the absorption of hydrogen. Effect of hydrogen on optical properties used in different applications such as gasochromic (Huiberts et al 1996), electrochromic (Notten et al 1996;Armitage et al 1999) or chemochromic (Vander Sluis et al 1999), photochromic (Hoekstra et al 2001), piezochromic (Wijngaarden et al 2000) and thermochromic (Giebles et al 2002). These materials are also interesting for hydrogen storage applications (Schlapbach and Zuttel 2002;Farangis et al 2003).…”
Section: Introductionmentioning
confidence: 95%